2023
DOI: 10.1088/1361-665x/acd506
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of soil water content using spherical smart aggregates based on electromechanical impedance (EMI) technique

Abstract: Real-time monitoring of soil water content is of great significance to prevent many engineering accidents, such as landslide, water seepage of foundation dam and reduction of foundation bearing capacity. Smart aggregates (SAs) based on electromechanical impedance (EMI) technique have showed the excellent monitoring capability in various engineering applications, however, there are limited reports on the application in the monitoring of the soil water content. In this paper, the spherical smart aggregates (SSAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 93 publications
(77 reference statements)
1
3
0
Order By: Relevance
“…To ensure the rationality of the results, the multiple specimens for the same experiment are tested, and the obtained results are consistent, which showed that the experiment is reliable. In addition, the earlier works have proved that the SSAs are more sensitive than the SAs in monitoring concrete hydration in very early age [53], soil water content [56], and damage of three-dimensional concrete structures [49], which indirectly indicate that the present results are reasonable. To further confirm the reliability of the present work, the numerical simulation based on the ANSYS software are conducted in this section.…”
Section: Numerical Simulation Based On the Ansys Softwaresupporting
confidence: 59%
See 2 more Smart Citations
“…To ensure the rationality of the results, the multiple specimens for the same experiment are tested, and the obtained results are consistent, which showed that the experiment is reliable. In addition, the earlier works have proved that the SSAs are more sensitive than the SAs in monitoring concrete hydration in very early age [53], soil water content [56], and damage of three-dimensional concrete structures [49], which indirectly indicate that the present results are reasonable. To further confirm the reliability of the present work, the numerical simulation based on the ANSYS software are conducted in this section.…”
Section: Numerical Simulation Based On the Ansys Softwaresupporting
confidence: 59%
“…In this section, the preparation process of concrete specimens will be described in detail. The SSAs fabricated using the monolithic concrete encapsulation method [56] and the traditional SAs [73,74] are adopted. The photographs of physical prototypes of SAs and SSAs used are shown in figure 2.…”
Section: Emi Principlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Khan et al conducted numerical and experimental studies using EMI methods to predict the performance changes of concrete materials in real-time [28]. Lan et al employed EMI spectroscopy to monitor soil water content, which provides real-time information on moisture changes in the soil [29].…”
Section: Introductionmentioning
confidence: 99%